Emerging Adulthood, a Pre-adult Life-History Stage - Hochberg, Ze′ev; Konner, Melvin (Frontiers in Endocrinology, 2020)
The duration of human maturation has been underestimated; an additional 4-6-year pre-adult period of 'emerging adulthood', should be included in models of human maturation. It is a period of brain maturation, learning intimacy and mutual support, intensification of pre-existing friendships, family-oriented socialization, and the attainment of those social skills that are needed for mating and reproduction. We propose that emerging adulthood is a life-history stage that is the foundation of the high reproductive success of human beings. The period of emerging adulthood has an evolutionary context and developmental markers, and we present evidence that supports the idea that emerging adults require protection because they are still learning and maturing.